Software-only Compression, Rendering, and Playback of Digital Video - Bahl, Victor; Gauthier, Paul S.; Ulichney, Robert A. (Digital, 1995)
Software-only digital video involves the compression, decompression, rendering and display of digital video on general-purpose computers without specialized hardware. Today`s faster processors are making software-only video an attractive, low-cost alternative to hardware solutions that rely on specialized compression boards and graphics accelerators. This paper describes the building blocks behind popular ISO, ITU-T and ndustry-standard compression schemes, along with some novel algorithms for fast video rendering and presentation. A platform-independent software architecture that organizes the functionality of compressors and renderers into a unifying software interface is presented. This architecture has been successfully implemented on the Digital UNIX, OpenVMS and Microsoft Windows NT operating systems. To maximize the performance of codecs and renderers, issues pertaining to flow control, optimal use of available resources and optimizations at the algorithmic, operating system and processor levels are considered. The performance of these codecs on Alpha systems is evaluated, and the ensuing results validate the potential of software-only solutions. Finally, this paper provides a brief description of some sample applications built on top of the software architecture, including an innovative video screen saver and a software VCR capable of playing multiple compressed bit streams.